TINJAUAN TENTANG KEKUATAN HUKUM POLIS ELEKTRONIK DALAM PERJANJIAN MENURUT KITAB UNDANG-UNDANG HUKUM DAGANG (KUHD) DAN UNDANG-UNDANG 40 TAHUN 2014 TENTANG PERASURANSIAN - Yoshua Jonathan Saputra; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2022)
Overview of the Legal Power of Electronic Policies in the Commercial Code Agreement and Law 40 of2014 concerning Insurance, resulting in the public having to prepare for the emergence of online-basedinsurance. According to Law 40 of 2014 concerning Insurance, in the era of technological growth there isstill no regulation that clearly handles the electronic policy problem. So that people are still confused,based on Article 1320 of the Civil Code, e-policy as a form of agreement generally has fulfilled the legalrequirements of the agreement based on Article 1320 of the Civil Code. However, as a form of e-policyagreement, it is also regulated in the Commercial Code. Meanwhile, based on Article 255 of theCommercial Code, the coverage must be in writing with a deed, which is given the name of the policy. Sothat the e-policy can be interpreted as not fulfilling the requirements for the validity of the fourthagreement, namely a lawful cause because e-policy is contrary to the Commercial Code which isequivalent to the Act. So that the insurance agreement can be interpreted as not meeting the objectiverequirements of an agreement, the agreement is null and void. Furthermore, the research method is foracademic purposes, the research method contains a description of the nature of the research, the methodsused to research, the data collection tools used in researching, research interviews and the types of data tobe obtained.